Highly reactive photothermal initiating system based on sulfonium salts for the photoinduced thermal frontal cationic polymerization of epoxides: a way to create carbon-fiber reinforced polymers. Issue 68 (18th November 2020) - Gachet, Benoit; Lecompère, Maxime; Croutxé-Barghorn, Céline; Burr, Dominique; L'Hostis, Gildas; Allonas, Xavier
Abstract : Photoinduced thermal frontal polymerization of epoxides made possible by use of a dual-cure initiating system based on sulfonium salts. Abstract : A new combination of sulfonium salts has been investigated to cure opaque and thick carbon composite materials through photoinduced thermal frontal polymerization reaction. The photopolymerization occurs at the surface of the cycloaliphatic epoxide through the excitation of a triarylsulfonium salt and releases enough heat to decompose an alkyl-based sulfonium salt acting as a latent thermal initiator. Thus, a thermal front propagates into the medium leading to the polymerization of the whole sample. Thermal properties and optimal parameters are investigated to obtain frontal polymerization in the depth of the material. Front velocities were as high as 12.9 cm min −1 and were found to increase with an increasing concentration of thermal sulfonium salt. The effect of an addition of carbon filler is investigated with a concentration of up to 50 wt%, which allows the formation of a composite material with a high content of carbon without the need for thermal post curing.